Validation of seven risk scores in a prospective and independent cohort: the challenge of predicting recurrence after atrial fibrillation ablation. (19th May 2022) - Filipovic, K; Dittrich, S; Scheurlen, C; Arica, Z; Erlhoefer, S; Woermann, J; Van Den Bruck, JH; Sultan, A; Steven, D; Lueker, J
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Several predictive scores for atrial fibrillation (AF) recurrence after ablation have been developed, only some of these are validated in prospective cohorts. The predictive value of such scores has thus far been limited, and many have not been compared with one another. Aims: We sought to compare the predictive value of seven previously described risk scores ((CHA2DS2 and CHA2DS2-VASC, HATCH, APPLE, CAAP-AF, BASE-AF2, MB-LATER) for prediction of AF recurrence risk at 12 months after AF ablation. Further, we aimed to identify additional variables to predict recurrences after AF ablation. Methods: We analyzed data from of our prospective digital AF ablation registry to compare the previously published scores in an independent and prospective cohort (n=883, 50.8% with paroxysmal AF). Patients were undergoing de-novo ablation of AF received a pulmonary vein isolation (PVI) using radiofrequency (RF) ablation or cryoablation. Ablation procedures for recurrences of AF after initial PVI included re-isolation of the pulmonary veins by RF ablation, with additional substrate modification at the operators' discretion. Early recurrence and recurrence after ablation were defined as any AF or atrial tachycardia episode lasting ≥ 30 s in the first 3 months after ablation and from the end of the 3-month period to 12 months after ablation. Follow-up of patients was scheduled at regular intervals 3 and 12 months after ablation, and included Holter-ECG, 12-lead ECG and history. Outcome-relevant data from implanted cardiac devices (CIED), such as 2-chamber ICD and pacemakers, or implantable loop recorders were analyzed when available. A predefined subgroup analysis was performed in the following subgroups: first procedure vs. redo procedure, paroxysmal vs. persistent AF, and RF ablation vs. cryoablation. Results: The BASE-AF2 (AUC 0.630, p<0.001), MB-LATER (AUC 0.612, p<0.001) CAAP-AF (AUC 0.591, p<0.001), APPLE (AUC 0.591, p<0.001) and CHA2DS2-VASC (AUC 0.547, p=0.018) scores had a significant but modest predictive value for 12-month AF-recurrence. None of these scores was significantly superior. Other previously published scores had no predictive value. There was no difference in the predictive value for 12-month recurrence of AF between first procedure vs. redo procedure and RF ablation vs. cryoablation. Unlike other scores, MB-LATER showed better predictive value for paroxysmal vs. persistent AF (AUC 0.632 vs. 0.551, p=0.038). In the multivariate logistic regression, only age (p=0.006), number of prior electrical cardioversions (p<0.001) and early AF recurrence (p<0.001) were independent predictors of 12-month AF recurrence. Conclusion: Despite numerous available scores, predicting recurrences after AF ablation remains challenging. New simple and robust predictors are needed, potentially based on diagnostic interventions, as well as novel genetic, functional and anatomic parameters.